2008
DOI: 10.1038/sj.ki.5002776
|View full text |Cite
|
Sign up to set email alerts
|

Early steroid treatment improves the recovery of renal function in patients with drug-induced acute interstitial nephritis

Abstract: The role of steroid treatment in drug-induced acute interstitial nephritis (DI-AIN) is controversial. We performed a multicenter retrospective study to determine the influence of steroids in 61 patients with biopsy-proven DI-AIN, 52 of whom were treated with steroids. The responsible drugs were antibiotics (56%), non-steroidal anti-inflammatory drugs (37%) or other drugs. The final serum creatinine was significantly lower in treated patients while almost half of untreated patients remained on chronic dialysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
291
2
25

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(341 citation statements)
references
References 11 publications
13
291
2
25
Order By: Relevance
“…A retrospective study examined the effects of steroids on the recovery of the renal function in 52 patients with druginduced acute interstitial nephritis compared to that observed in nine untreated patients with acute interstitial nephritis. The significant benefits observed with steroids included a lower rate of the need for dialysis by 18 months (4% vs. 44%) and lower serum creatinine levels [2.1 vs. 3.7 mg/ dL (18)]. On the other hand, another retrospective study of 42 cases of acute interstitial nephritis demonstrated no benefits from glucocorticoid therapy.…”
Section: Discussionmentioning
confidence: 98%
“…A retrospective study examined the effects of steroids on the recovery of the renal function in 52 patients with druginduced acute interstitial nephritis compared to that observed in nine untreated patients with acute interstitial nephritis. The significant benefits observed with steroids included a lower rate of the need for dialysis by 18 months (4% vs. 44%) and lower serum creatinine levels [2.1 vs. 3.7 mg/ dL (18)]. On the other hand, another retrospective study of 42 cases of acute interstitial nephritis demonstrated no benefits from glucocorticoid therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have suggested a positive influence on the complete recovery of renal function in those patients who received steroids [17][18][19]. A multicenter study of González et al [20] showed that, in biopsy-proven DI-AN patients, final creatinine levels were found to be better (lower) in the steroid administered group than in the nonsteroid (control) group. Also, according to that study, the final serum creatinine level and renal pathology were affected negatively if steroid treatment was started late (2 weeks after withdrawal of the presumed causative drug).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we focus on direct drug-induced effects on the proximal tubule cell, the thick ascending limb cell, the collecting duct principal cell and the collecting duct intercalated cell. Mechanisms of acute kidney failure due to tubular necrosis and interstitial nephritis caused by antibiotics are beyond the scope of this review and are reviewed elsewhere [21,22]. First, we give a short summary of the pathophysiology of the different disorders of acid-base homeostasis based on the different findings in analysis of arterial or, if not available, venous blood gases, which is usually the first diagnostic step in everyday clinical practice (Fig.…”
Section: Introductionmentioning
confidence: 99%